Making a Difference—Positive Effect of Unilateral VIM Gamma Knife Thalamotomy in the Therapy of Tremor in Fragile X-Associated Tremor/Ataxia Syndrome (FXTAS) - Alster, Piotr; Koziorowski, Dariusz M.; Za̧bek, Mirosław; Dzierzȩcki, Sebastian; Ma̧dry, Jacek; Duszyńska-Wa̧s, Karolina; Grygarowicz, Hanna; Zielonko, Justyna; Królicki, Leszek; Friedman, Andrzej (Frontiers in Neurology, 2018)
Fragile X Tremor Ataxia Syndrome (FXTAS) is a syndrome based on expansion of the repeats of CGG triplets. The symptoms include action tremor and cerebellar gait ataxia. Additionally symptomatology of FXTAS may be associated to parkinsonism, executive function deficits, dementia, neuropathy and dysautonomia. We present a case of a patient who after 20 year history of progressive tremor and ataxia, was diagnosed after genetic examination as mutation of FXTAS. For the treatment of tremor the patient underwent Gamma Knife (GK) thalamotomy. Reduced tremor on the right side and improvement in everyday activities were observed in the outcome of the treatment. GK thalamotomy, in the context of this patient, did not significantly affect the ataxia.